Proposing a strategic transformation model for universities (Case study: A public university) - Zahra Bagheri; Seyed Javad Hosseininezhad; Nasser Safaie (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to implement and change the administrative system using conventional methods and build a strategic transformation model for universities.Methodology: The present research method is qualitative. By examining the organization's strategic plan, identifying the effective indicators, and ranking the components based on a multi-criteria decision-making method, TOPSIS, the final transformation model has been prepared using the interpretive structure model (ISM). Findings: By studying the strategic planning developed for the organization, the main components were determined, and using the ISM technique, the main components of levelling. Finally, the transformation model was considered at four levels. Finally, it was observed that knowledge management is at level 1 and affects other barriers. Also, the environment of change, competitors, and effective communication with the industry are influenced by different factors and do not affect other factors.Originality/value: Traditional management and leadership methods lack effectiveness in today's changing and dynamic conditions. Considering that university administrators are the primary decision-makers, paying attention to their managerial capabilities significantly impacts the success of the country's higher education system.